A developmentally regulated membrane protein gene in Dictyostelium discoideum is also induced by heat shock and cold shock. - Maniak, M (1988)
We have analyzed the expression of the Dictyostelium gene P8A7 which had been isolated as a cDNA clone from an early developmentally regulated gene. The single genomic copy generated two mRNAs which were subject to different control mechanisms: while one mRNA (P8A7S) was regulated like the cell-type-nonspecific late genes, the other one (P8A7L) was induced during development, when cells were allowed to attach to a substrate, and when cells were subjected to stress, such as heat shock and cadmium. Interestingly the same induction was also observed with cold shock. RNA processing was inhibited by heat and cold shock, leading to nuclear accumulation of a precursor. The translated region of the cDNA was common to both mRNAs and encoded an unusually hydrophobic peptide with the characteristics of a membrane protein.